2020
DOI: 10.2478/hepo-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant status and hepato-protective role of Anchomanes difformis in streptozotocin-induced diabetes in male Wistar rats

Abstract: SummaryIntroduction: The liver is involved in the metabolism of xenobiotics and their metabolites and it is vulnerable to oxidative damage. Hyperglycaemia is highly implicated in the progression of diabetes mellitus, and adversely affects the liver. Though, conventional hypoglycaemic drugs may be effective in reducing blood glucose, they do not appear to be effective in attenuating the progression of diabetes and its complications.Objective: This study evaluated the ameliorative effects of Anchomanes difformis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…The wide range of biological properties of compounds present in AD has necessitated the need to further investigates its potentials against diabetes and diabetic complications. Our research works then investigated, established and reported the antidiabetic ability of AD aqueous extract [ 27 ], which led to further explore the attenuating ability of AD diabetic complications involving the liver, heart and the reproductive system [ 27 , 28 , 29 ]. However, no study has been conducted to investigate the potency of AD leaves on the kidney and pancreas pathology in diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…The wide range of biological properties of compounds present in AD has necessitated the need to further investigates its potentials against diabetes and diabetic complications. Our research works then investigated, established and reported the antidiabetic ability of AD aqueous extract [ 27 ], which led to further explore the attenuating ability of AD diabetic complications involving the liver, heart and the reproductive system [ 27 , 28 , 29 ]. However, no study has been conducted to investigate the potency of AD leaves on the kidney and pancreas pathology in diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Diabetes Federation (IDF) report, 10 th edition 2021, 537 million adults aged 20 to 75 are living with diabetes and approximately 6.7 million deaths are attributed worldwide 2 . Organ dysfunction in the liver, heart, kidneys, blood vessels, urogenital tract system, and eyes is a common complication of type 2 diabetes mellitus 3 . Chronic hyperglycemia is associated with a decrease in antioxidant status, an increase in reactive oxygen species formation, and dyslipidemia 4 .…”
Section: Introductionmentioning
confidence: 99%